CD8+ T-cell immune escape by SARS-CoV-2 variants of concern - Kombe Kombe, Arnaud John; Biteghe, Fleury Augustin Nsole; Ndoutoume, Zélia Nelly; Jin, Tengchuan (Frontiers in Immunology, 2022)
Despite the efficacy of antiviral drug repositioning, convalescent plasma (CP), and the currently available vaccines against the SARS-CoV-2, the worldwide COVID-19 pandemic is still challenging because of the ongoing emergence of certain new SARS-CoV-2 strains known as variants of concern (VOCs). Mutations occurring within the viral genome, characterizing these new emerging VOCs confer to them the ability to efficiently resist and escape natural and vaccine-induced humoral and cellular immune responses. Consequently, these VOCs have enhanced infectivity, increasing their stable spread in a given population, with an important fatality rate. While the humoral immune escape process is well documented, evasion mechanisms of VOCs from cellular immunity are not well elaborated. In this review, we discussed how SARS-CoV-2 VOCs adapt inside host cells and escape anti-COVID-19 cellular immunity with a focus on the effect of specific SARS-CoV-2 mutations in hampering activation of CD8+ T-cells immunity.